The Efforts of the Palu Odoj Community in Creating a Generation of Al-Quran Love for Odoj Members of Palu City, Central Sulawesi (Case Study: Secretariat Odoj Palu)) - Eka Firmansyah; Abdul Mufarik A. Marhum; Muh. Rizal Masdul (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
The Qur'an is the noblest holy book, which was revealed to the noblest Apostle, through the intercession of the noblest angels, to be a guide for the noblest ummah. This article discusses the efforts made by the Palu ODOJ Community in creating a generation of Al-Qur'an love among ODOJ members, Palu City, Central Sulawesi. It describes how the Palu ODOJ Community is trying to become the background for the increasing love of the Qur'an for ODOJ members of Palu City itself. The results of this study indicate that the efforts made by the Palu ODOJ Community are very influential in increasing the love of the Qur'an in this generation, especially for those who are members of the Palu City ODOJ Community, which in achieving this goal, the Palu ODOJ Community made several efforts, namely: (1) requiring one day to read the Koran one juice (2) holding monthly recitations (3) holding out-door recitations (4) holding recitations in the school environment (5 ) held recitations in the campus environment. With these efforts, they can have several impacts on the members of ODOJ Palu themselves, such as: (1) becoming accustomed to continue reading the Qur'an one day one juice, (2) increasing motivation to continue to recite the Qur'an. An, (3) a change in the rigid impression on the activities of reading the Qur'an which has been influencing the minds of Muslims, (4) the creation of generations of love of the Koran in schools, (5) the creation of a generation of love for the Koran Qur'an on campuses.